Phenotypic Displays of Cholinergic Enzymes Associate With Markers of Inflammation, Neurofibrillary Tangles, and Neurodegeneration in Pre- and Early Symptomatic Dementia Subjects - Teitsdottir, Unnur D.; Darreh-Shori, Taher; Lund, Sigrun H.; Jonsdottir, Maria K.; Snaedal, Jon; Petersen, Petur H. (Frontiers in Aging Neuroscience, 2022)
Background: Cholinergic drugs are the most commonly used drugs for the treatment of Alzheimer’s disease (AD). Therefore, a better understanding of the cholinergic system and its relation to both AD-related biomarkers and cognitive functions is of high importance. Objectives: To evaluate the relationships of cerebrospinal fluid (CSF) cholinergic enzymes with markers of amyloidosis, neurodegeneration, neurofibrillary tangles, inflammation and performance on verbal episodic memory in a memory clinic cohort. Methods: In this cross-sectional study, 46 cholinergic drug-free subjects (median age=71, 54% female, median MMSE=28) were recruited from an Icelandic memory clinic cohort targeting early stages of cognitive impairment. Enzyme activity of acetylcholinesterase (AChE) and butyrylcholinesterase (BuChE) was measured in CSF as well as levels of amyloid-β1–42 (Aβ42), phosphorylated tau (P-tau), total-tau (T-tau), neurofilament light (NFL), YKL-40, S100 calcium-binding protein B (S100B) and glial fibrillary acidic protein (GFAP). Verbal episodic memory was assessed with the Rey Auditory Verbal Learning (RAVLT) and Story tests. Results: No significant relationships were found between CSF Aβ42 levels and AChE or BuChE activity (p>0.05). In contrast, T-tau (r=0.46, p=0.001) and P-tau (r=0.45, p=0.002) levels correlated significantly with AChE activity. Although neurodegeneration markers T-tau and NFL did correlate with each other (r=0.59, p<0.001), NFL did not correlate with AChE (r=0.25, p=0.09) or BuChE (r=0.27, p= p=0.06). Inflammation markers S100B and YKL-40 both correlated significantly with AChE (S100B: r=0.43, p=0.003; YKL-40: r=0.32, p=0.03) and BuChE (S100B: r=0.47, p<0.001; YKL-40: r=0.38, p=0.009) activity. A weak correlation was detected between AChE activity and the composite score reflecting verbal episodic memory (r=-0.34, p=0.02). LASSO regression analyses with a stability approach were performed for the selection of a set of measures best predicting cholinergic activity and verbal episodic memory score. S100B was the predictor with the highest model selection frequency for both AChE (68%) and BuChE (73%) activity. Age (91%) was the most reliable predictor for verbal episodic memory, with selection frequency of both cholinergic enzymes below 10%. Conclusions: Results indicate a relationship between higher activity of the ACh-degrading cholinergic enzymes with increased neurodegeneration, neurofibrillary tangles and inflammation in the stages of pre- and early symptomatic dementia, independent of CSF Aβ42 levels.